Stability of Schistosoma mansoni progeny to antischistosomal drugs - Luiz Candido de Souza Dias; Celso Eduardo Olivier (Revista do Instituto de Medicina Tropical de São Paulo, 1985)
The susceptibility of the MAP Brazilian strain (F1 to F5 progenies) of S. mansoni to four antischistosomal drugs has been reported in a previous study. In the present investigation, progeny F14 of the same strain, was tested for stability to the same 4 drugs. A new medication, Oltipraz (35,972 RP), was added to the study. Five groups of 12 mice infected with cercariae by tail immersion were treated with hycanthone, oxamniquine, niridazole, praziquantel and Oltipraz. An untreated group was used as control. Schistosomal activity was assessed by the localization of worms in the portal vein system, by oogram changes, and percentage of parasite reduction. The stability of the susceptibility of progeny F14 did not change in relation to generations F1 to F5; the progeny was resistant to hycanthone and oxamniquine; but sensitive to niridazole, praziquantel and Oltipraz. We emphasize the importance of the phenomenon of resistance of the worm in view of the fact that oxamniquine has been widely used in Brazilian areas where mansonic schistosomiasis is endemic.